Alcohol consumption in Mexican high school students - Puig-Lagunes, Ángel Alberto; Nolasco, Ángel Puig; Mendez, Luis Enrique Salinas; Álvarez, Jesús Enrique Vargas; Pillon, Sandra Cristina (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2019)
Objective: to evaluate the consumption pattern and the perceptions about alcohol use by people close to the Mexican high school students. Method: this is a crosssectional and quantitative approach, involving 940 students from six bachelors courses in the State of Veracruz, Mexico. Outcomes: prevalence of use was 57.4% in life, 31.5% in the last year, 25.3% in the last month; 7.4% consumed alcohol on a problematic level. Negative perceptions about alcohol consumption were evaluated by fathers and mothers, predominantly among students with low risk consumption. Conclusion: alcohol consumption among baccalaureate students is high, especially among men, with an earlier onset and incidence of intoxication. In addition, it is very present among students with problems in parental relationships. The results may support the development of preventive programs in relation to alcohol consumption in school settings.